2020
DOI: 10.1007/s42452-020-03749-0
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic contamination of salt intended for human consumption: a systematic review and meta-analysis

Abstract: Microplastics (MPs) are an emerging contaminant ubiquitous in the environment. There is growing concern regarding potential human health effects, a major human exposure route being dietary uptake. We have undertaken a systematic review (SR) and meta-analysis to identify all relevant research on MP contamination of salt intended for human consumption. Three thousand nine hundred and nineteen papers were identified, with ten fitting the inclusion criteria. A search of the databases MEDLINE, EMBASE and Web of Sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 105 publications
0
19
0
Order By: Relevance
“…A recent study by Guillen et al (2019) attempted to calculate the global seafood production and consumption footprint using FAO consumption data and modeling, reporting China to be the major global producer and consumer and also as being self-sufficient for the most part (Guillen et al 2019). Other media have also been identified as vectors of MPs via the ingestion route with varying MP concentrations, such as sugar (0:44 MPs=g) (Cox et al 2019), whereas in our previous work, salt was found to have an MP content of 0-1,674 MPs=kg (Danopoulos et al 2020a), tap water 0-628 MPs=L, and bottled water 0-4,889 MPs=L (Danopoulos et al 2020b). Further systematic reviews are needed to robustly assess MP contamination and human exposures from all food categories.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…A recent study by Guillen et al (2019) attempted to calculate the global seafood production and consumption footprint using FAO consumption data and modeling, reporting China to be the major global producer and consumer and also as being self-sufficient for the most part (Guillen et al 2019). Other media have also been identified as vectors of MPs via the ingestion route with varying MP concentrations, such as sugar (0:44 MPs=g) (Cox et al 2019), whereas in our previous work, salt was found to have an MP content of 0-1,674 MPs=kg (Danopoulos et al 2020a), tap water 0-628 MPs=L, and bottled water 0-4,889 MPs=L (Danopoulos et al 2020b). Further systematic reviews are needed to robustly assess MP contamination and human exposures from all food categories.…”
Section: Discussionmentioning
confidence: 76%
“…Other media have also been identified as vectors of MPs via the ingestion route with varying MP concentrations, such as sugar ( ) ( Cox et al. 2019 ), whereas in our previous work, salt was found to have an MP content of ( Danopoulos et al. 2020a ), tap water , and bottled water ( Danopoulos et al.…”
Section: Discussionmentioning
confidence: 79%
“…In the last few years, several studies regarding the microplastic contamination of salt intended for human consumption [ 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ] have been published and discussed [ 171 , 172 , 173 , 174 ]. Salts provide essential nutrition elements and, thanks to their chemical characteristics and low cost, are used in food preservation methods (e.g., fruits, cheese, cereals, drinks).…”
Section: Microplastic Transport In the Food Web And Consequent Human Exposurementioning
confidence: 99%
“…Danopoulos and colleagues also recently published systematic reviews of microplastics exposure from salt 6 and drinking water. 7 They estimated potential human exposures via salt at 0–6,110 MPs/year.…”
mentioning
confidence: 99%
“… 7 They estimated potential human exposures via salt at 0–6,110 MPs/year. 6 For drinking water, they estimated that people might be consuming up to 458,000 MPs/year for tap water and 3,569,000 MPs/year for bottled water, based on average water consumption. 7 “The results of all three systematic reviews,” Danopoulos says, “can be used in an aggregate exposure framework from all three mediums, which will give us an estimate of high confidence on human microplastics exposures.”…”
mentioning
confidence: 99%